Inventarisasi Kondisi Jaringan Irigasi pada Saluran Irigasi Bendung Metukul Kanan Daerah Irigasi Rias: Inventory of Irrigation Network Conditions in The Metukul Kanan Irrigation Channel-Rias Irrigation Area - Frapas, Frapas Segara; Hambali, Roby; Sandy, Boy Dian Anugra (Himpunan Ahli Teknik Hidraulik Indonesia (HATHI), 2025)
The Rias Irrigation Area is the largest irrigation area on Bangka Island. From 2020 to 2023, its irrigation channels have not been maintained, especially the right intake channel served by the Metukul Dam. Maintenance includes evaluating the condition and function of irrigation assets, including evaluating the structure of the channel, sluice gates, and measuring structures. The irrigation channel is 6,475 m long and has a service area of ​​4,202 Ha. The channel consists of nine segments that begin with sluice gates separating each segment. This study aims to inventory the condition and function of irrigation assets and determine the priority value of irrigation asset maintenance in the Rias Irrigation Area. The asset survey was carried out by tracing the irrigation network and identifying damage based on the condition assessment form. After that, the condition of the components was calculated according to the type of construction (Structure, sluice gate, measuring structure). The results of the inventory of irrigation assets in the Metukul Kanan channel show that the condition of the channel structure scored 4 (good), the condition of the water gate scored 3.7 (lightly damaged), the function of the channel structure scored 3.1 (good). The function of the water gate scored 3.7 (good). The calculation results of the irrigation assets condition scored 3.01 (lightly damaged), and the function value of irrigation assets scored 2.69 (poor). The condition and function values ​​of the measuring structure were scored 1 (severely damaged/bad) because no measuring structure was found in the irrigation channel. The function of the channel shows that the individual performance value of the network assets is 82% in the good performance category, with a damage index of 1.109% for the physical condition of the irrigation channel.